Jimmy Carter [videorecording (DVD)] : rock & roll President (Kino Lorber, 2020)
If it hadn't been for a bottle of scotch and a late-night visit from musician Gregg Allman, Jimmy Carter might never have been elected the 39th President of the United States. This documentary charts the mostly forgotten story of how Carter, a lover of all types of music, forged a tight bond with musicians Willie Nelson, the Allman Brothers, Bob Dylan and others.